1988
DOI: 10.1007/bf03350134
|View full text |Cite
|
Sign up to set email alerts
|

The different types of hyperthyroidism in Europe. Results of a prospective survey of 924 patients

Abstract: In a prospective multicentric study, 924 untreated hyperthyroid patients were investigated, coming consecutively within one year into 17 thyroid centers of 6 European countries. With the aid of clinical information, evaluation of thyroid scan and centrally assayed thyroid hormones, thyroid antibodies, TSH-binding inhibiting immunoglobulins (TBII), and urinary iodine, different types of hyperthyroidism could be shown. Two types of hyperthyroidism could be defined directly: autonomous adenoma in cases of hot nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(34 citation statements)
references
References 14 publications
6
23
0
5
Order By: Relevance
“…In this study, comparing ten nosological types of thyrotoxicosis, GD patients presented the highest T 3 level and T 3 :T 4 ratio, which is in accordance with other studies (4,22,23,25). Similarly, amiodarone-associated thyrotoxicosis was dominated by high serum T 4 levels as previously reported by Martino et al (26).…”
Section: Serum T 3 and T 4 In Subtypes Of Thyrotoxicosissupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, comparing ten nosological types of thyrotoxicosis, GD patients presented the highest T 3 level and T 3 :T 4 ratio, which is in accordance with other studies (4,22,23,25). Similarly, amiodarone-associated thyrotoxicosis was dominated by high serum T 4 levels as previously reported by Martino et al (26).…”
Section: Serum T 3 and T 4 In Subtypes Of Thyrotoxicosissupporting
confidence: 92%
“…Many studies have reported T 3 and T 4 levels in patients diagnosed with all types of thyrotoxicosis combined (20) or in a few (4,21,22,23) or even up to four nosological subtypes of thyrotoxicosis (24). In this study, comparing ten nosological types of thyrotoxicosis, GD patients presented the highest T 3 level and T 3 :T 4 ratio, which is in accordance with other studies (4,22,23,25).…”
Section: Serum T 3 and T 4 In Subtypes Of Thyrotoxicosissupporting
confidence: 92%
See 2 more Smart Citations
“…Other studies only evaluated certain age groups (8). Most studies were based on patients referred to hospital departments (6,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), potentially leading to referral bias (19).…”
Section: Introductionmentioning
confidence: 99%